Development Model and Small Medium Industry Strategy in Gerbang Kertosusilo Indonesia - Suratman, Bambang; Soesatyo, Yoyok; Sulistyowati, Raya; Subroto, Waspodo Tjipto (International Review of Management and Marketing, 2017)
Small medium industry in Gerbangkertosusilo specifically in Surabaya, Gresik, Mojokerto and Sidoarjo based on development acceleration importance until 2025 in those areas are food and beverage industry developing. Strategic analysis required in identify small and medium enterprises industry cited to resulting in relevant strategy model. Analysis had done by using strength, weakness, opportunities, threats analysis with identify external and interal factors included production management, human resource management, financial management and marketing management. Data identified qualitatively and quantitively to drawing conclusion about relevant model and strategy. Keywords: Small and Medium Enterprises, Production, Human Resources, Marketing Management JEL Classifications: M11, M31, O15